2022
DOI: 10.1523/eneuro.0025-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Robust, Long-Term Video EEG Monitoring in a Porcine Model of Post-Traumatic Epilepsy

Abstract: To date, post-traumatic epilepsy (PTE) research in large-animal models has been limited. Recent advances in neocortical microscopy have made possible new insights into neocortical PTE. However, it is very difficult to engender convincing neocortical PTE in rodents. Thus, large-animal models that develop neocortical PTE may provide useful insights that also can be more comparable to human patients. Because gyrencephalic species have prolonged latent periods, long-term video EEG recording is required. Here, we r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The PDMS iteration in this case had a silicone ring/ “hat” attached to line the burr hole and more difficult to place. There was a large space-filling hemorrhage under the PDMS membrane in an animal that had previously placed skull screws for EEG 19 perhaps limiting movement and accommodation of the brain to the hematoma. Placing the PDMS membrane does present a risk of laceration of cortical veins and re-bleeding after skin closure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PDMS iteration in this case had a silicone ring/ “hat” attached to line the burr hole and more difficult to place. There was a large space-filling hemorrhage under the PDMS membrane in an animal that had previously placed skull screws for EEG 19 perhaps limiting movement and accommodation of the brain to the hematoma. Placing the PDMS membrane does present a risk of laceration of cortical veins and re-bleeding after skin closure.…”
Section: Resultsmentioning
confidence: 99%
“…Two swine (18 months of age, 76 - 84 kg) had received cortical impact 12 months prior to imaging. One pig had developed post-traumatic epilepsy; both were imaged to determine Cl o 10 . The cranial imaging windows were observed in 2 pigs 3.5 month after installation.…”
Section: Methodsmentioning
confidence: 99%
“…While wearable devices are desirable for human patients, pigs are curious and often chew anything they can reach, thus some studies may facilitate a need for implantable monitoring equipment. Martinez-Ramirez et al (2022) demonstrated the capability of subdural implanted EEG monitoring systems for the long-term assessment of post-traumatic epilepsy in freely ambulating pigs for up to 13 months [ 52 ]. As a whole, pigs provide a fantastic model in which to test the validity of various novel devices or to use pre-established technologies for comparison to human data.…”
Section: Reviewmentioning
confidence: 99%